Strength Training Session Induces Important Changes on Physiological, Immunological, and Inflammatory Biomarkers - Ayla Karine Fortunato; Washington Martins Pontes; Débora Maria Soares De Souza; Jéssica Santos Ferreira Prazeres; Lucas Soares Marcucci-Barbosa; Júlia Miranda Mól Santos; Érica Leandro Marciano Veira; Eduardo Bearzoti; Kelerson Mauro De Castro Pinto; André Talvani; Albená Nunes Da Silva (Journal of Immunology Research)
Strength exercise is a strategy applied in sports and physical training processes. It may induce skeletal muscle hypertrophy. The hypertrophy is dependent on the eccentric muscle actions and on the inflammatory response. Here, we evaluate the physiological, immunological, and inflammatory responses induced by a session of strength training with a focus on predominance of the eccentric muscle actions. Twenty volunteers were separated into two groups: the untrained group (UTG) and the trained group (TG). Both groups hold 4 sets of leg press, knee extensor, and leg curl at 65% of personal one-repetition maximum (1RM), 90 s of recovery, and 2″conc/3″eccen of duration of execution in each repetition. Blood samples were collected immediately before and after, 2 hours after, and 24 h after the end of the exercise session. The single session of strength training elevated the heart rate (HR), rating of perceived exertion (RPE), visual analog scale (VAS), and lactate blood level in UTG and TG. Creatine kinase (CK) levels were higher at 2 and 24 h after the end of the exercise in UTG and, in TG, only at 24 h. The number of white blood cells (WBC) and neutrophils increased in UTG and TG, post and 2 h after exercise. Lymphocytes increased postexercise but reduced 2 h after exercise in both groups, while the number of monocytes increased only immediately after the exercise session in UTG and TG. The strength training session elevated the levels of apelin and fatty acid-binding proteins-3 (FABP3) in both groups and brain-derived neurotrophic factor (BDNF) in TG. The single exercise session was capable of inducing elevated HR, RPE, lactate level, and CK levels. This protocol changed the count/total number of circulating immune cells in both groups (UTG and TG) and also increased the level of plasmatic apelin, BDNF, and FLTS1 only in TG and FABP3 myokines in both groups.